2019
DOI: 10.1021/acs.jpcc.8b11255
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Lithium Adsorption and Diffusion toward Extraordinary Lithium Storage Capability of Freestanding Ti3C2Tx MXene

Abstract: Chemical etching method shows potential for large-scale and low-cost processed MXenes but incorporates surface terminations such as F&OH that probably deteriorate the lithium storage characteristics. Herein, we propose that tailoring appropriate surface functionalization and the intrinsic electrical properties can dramatically enhance the lithium storage capability of Ti3C2T x (T stands for F, OH, and O) MXene materials. By carefully controlling the annealing process, the Ti3C2T x films  possess fewer F&OH e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 46 publications
2
39
0
1
Order By: Relevance
“…However, with an enlarged interlayer distance benefitting the ionic accessibility, Nat-0.5 exhibits a reversible capacity of 351 mAh g −1 , more than twice that of Vac-0.5 and close to the theoretical capacity of Ti 3 C 2 . In addition, the initial Coulombic efficiency of Nat-0.5 is 56.5%, similar to that of Vac-0.5, which is a common value for MXene anode materials [ 20 , 21 ] and indicates that the enlarged interlayer distance has little effect on the initial Coulombic efficiency. For Nat-2 and Nat-1, the reversible Li-storage capacities reach 191 and 328 mAh g −1 due to the expanded interlayer distance, showing a positive correlation between the capacity and the interlayer distance.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…However, with an enlarged interlayer distance benefitting the ionic accessibility, Nat-0.5 exhibits a reversible capacity of 351 mAh g −1 , more than twice that of Vac-0.5 and close to the theoretical capacity of Ti 3 C 2 . In addition, the initial Coulombic efficiency of Nat-0.5 is 56.5%, similar to that of Vac-0.5, which is a common value for MXene anode materials [ 20 , 21 ] and indicates that the enlarged interlayer distance has little effect on the initial Coulombic efficiency. For Nat-2 and Nat-1, the reversible Li-storage capacities reach 191 and 328 mAh g −1 due to the expanded interlayer distance, showing a positive correlation between the capacity and the interlayer distance.…”
Section: Resultsmentioning
confidence: 53%
“…However, similar to other 2D materials, the restacking phenomenon of Ti 3 C 2 T x flakes during the film fabrication process may decrease the ion accessibility and hinder their effective utilization. Thus, the reversible capacity for pristine MXene film is only 100-200 mAh g −1 [20][21][22], far from the theoretical value. Meanwhile, as the restacked large Ti 3 C 2 T x flakes seriously impede the ion diffusion by increasing the diffusion path, and lowering diffusion kinetics, which is unfavorable for the rate performance.…”
Section: Introductionmentioning
confidence: 71%
“…Regardless of the method used to prepare MXene, the etching results in F and OH surface functional groups owing to the presence of HF and water. Given the presence of 2D layers, MXene has been widely studied for its electrochemical applications and specifically for LIBs as an intercalation pseudocapacitor electrode . However, owing to the compact atomic arrangement of MXene that would hinder the diffusion of Li + perpendicular to the layer plane, the electrodes have a reduced power density .…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the methodu sed to prepare MXene,t he etchingr esults in Fa nd OH surface functional groups owing to the presence of HF and water.Given the presence of 2D layers,M Xeneh as been widely studied for its electrochemical applicationsa nd specifically forL IBs as an intercalation pseudocapacitore lectrode. [4][5][6][7][8][9][10] However,o wing to the compacta tomica rrangement of MXene that would hindert he diffusionofLi + perpendicular to the layer plane, the electrodes have areduced power density. [11] To increase the powerdensity of MXenes, Ma et al, [12] for example, prepared hybrid 3D porousM Xene/reduced graphene oxide films in which the 3D structure facilitates the diffusion of Li + .A nother possibility to enhancethe electrochemical performance of MXenee lectrodes is by changing their surfacef unctional groups:c alculations have shown that MXenes have at unable band gap controllable by changingt heir surface termination.…”
Section: Introductionmentioning
confidence: 99%
“…[172] In another report, Ti 3 C 2 T x films were annealed in N 2 /H 2 atmosphere for different periods of time from 0 to 12 hours. [173] As shown in Figure 15 (g), increasing annealing period shifted the Raman peaks (at 585 and 386 cm À 1 ) to lower wavenumbers, indicating that the content of Ti 3 C 2 F 2 and Ti 3 C 2 (OH) 2 was decreased while that of Ti 3 C 2 O 2 was increased. [173] The thin films were then applied as anodes for lithium-ion batteries and demonstrated an excellent capacity of above 220 mAh g À 1 at 32 mA g À 1 due to the reduced diffusion barrier for lithium ions and the decreased sheet resistance (from 0.4 � 0.02 to 0.17 � 0.01 Ω sq À 1 ) after the thermal treatment.…”
Section: Effect Of the Post-treatmentmentioning
confidence: 81%